Pendekatan Etnosains Dalam Proses Pembuatan Wogi Terhadap Kemampuan Literasi Sains Peserta Didik SMP Swasta Tananuwa Masabewa - Yohanista Nona Bogar; Yulimira Syafriati Y. M. Sani; Mariana Sada (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to determine the scientific literacy skills of Tananuwa Masabewa private junior high school students. This research was carried out at Tananuwa Masabewa Private Middle School in semester 2 of the 2022/2023 academic year. Meanwhile, the research question is how students' scientific literacy skills relate to the process of making wogi at Tananuwa Masabewa Private Middle School. The data sources in this study were all 30 class XI A students at Tananuwa Masabewa Private Middle School. The data collection methods that the researchers used in this study were observation, questionnaires, and documentation. To analyze the data, the researcher used a qualitative descriptive analysis with. Based on the percentage covered in this study, it can be seen that the scientific literacy ability of class XI A students in the Integrated Science subject at Tananuwa Masabewa Private Middle School is seen from three aspects with the following percentages: context aspect (25%), content aspect (86, 20%), competency aspect (88, 63%).